Export-Growth Dynamics in NICs: An Econometric Investigation - Athiyyah Nursyifa Tisnandar; Agung Permana; Zakaria, Rinny Apriliany; Dijan Rahajuni (Journal of Economics Development Issues, 2025)
In international economic studies, the relationship between exports and economic growth has long been a subject of debate. Two key hypotheses growth-led export and export-led growth have been proposed to explain this linkage. This study investigates the validity of both hypotheses in four ASEAN NICs (Indonesia, Thailand, Malaysia, and the Philippines) from 2000 to 2023 using the Granger Causality Test. It also examines the interaction between the two variables through a linear framework utilizing the Autoregressive Distributed Lag (ARDL) model. The Granger causality results indicate that economic growth causally influences exports, thereby supporting the growth-led export hypothesis in all four countries. Moreover, the ARDL findings reveal that economic growth exerts a positive impact on exports in both the short and long term. These results underscore the importance of promoting economic activity, particularly in productive sectors that can strengthen export performance.